A new crinoid from the Mississippian (Early Carboniferous) of South Pembrokeshire, Wales. (21st May 2013) - Howells, Cindy; Kammer, Thomas
<x xml:space="preserve">Abstract</x> A new species of cladid crinoid, Hylodecrinus cymrus, is described from the Pembroke Limestone Group (Mississippian, Tournaisian, Courceyan) of West Angle Bay in south Pembrokeshire, Wales. It has a medium bowl‐shaped aboral cup, with strong ridges extending across the basals and radials forming pits at the plate corners. It is most similar to the late Tournaisian H. carinatus (Hall, 1861) of North America but differs in having less strongly cuneate brachials that are longer than wide with more subtle carinae on the aboral side. This specimen represents the first report of this genus from Europe, which most probably migrated from North America. Copyright © 2013 John Wiley & Sons, Ltd.